Implikatur Percakapan dalam Film Sweet 20 Karya Ody C. Harahap - Sari, Deby Prana; Effendi, M. Syahrun (UNIB Press, 2020)
The purpose of this study was to describe the general conversational implicature, scale conversation implicature, and special conversation implicature in in the Sweet 20 film by Ody C. Harahap. The research method used is qualitative research methods. Data collection techniques used are documentation techniques and refer to techniques. Data analysis techniques by transcribing the entire contents of the film, marking implicature, interpreting, and making conclusions. Test the validity of the data with member checking and expert validity. From the results of the study, the dominant implicature used in the Sweet 20 film by Ody C. Harahap is a specific conversation implicator as much as 75%, followed by a general conversation implicator as much as 21.33%, and finally the scale implication as much as 3.79%. The specific implications of the conversation in the form of using the language of speakers tend to use special words that only the speaker can understand the meaning or purpose of the speech. The Sweet 20 film is personal and familial in delivering speeches by speakers. From the results of this study, what needs to be considered is that when writing films Indonesian language teachers should pay attention to the composition of the use of implicature types.